2020
DOI: 10.1001/jama.2020.9389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine on Left Ventricular Ejection Fraction in Patients With Subclinical Hypothyroidism and Acute Myocardial Infarction

Abstract: IMPORTANCE Thyroid hormones play a key role in modulating myocardial contractility. Subclinical hypothyroidism in patients with acute myocardial infarction is associated with poor prognosis.OBJECTIVE To evaluate the effect of levothyroxine treatment on left ventricular function in patients with acute myocardial infarction and subclinical hypothyroidism. DESIGN, SETTING, AND PARTICIPANTSA double-blind, randomized clinical trial conducted in 6 hospitals in the United Kingdom. Patients with acute myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
0
33
0
4
Order By: Relevance
“…Multiple studies have suggested improvement in cholesterol parameters, blood pressure, and various markers of cardiac and vascular structure/function with levothyroxine treatment in SCH (25,(57)(58)(59)(60)(61), but generally these studies were small, the results need to be replicated, and any improvement in CVD risk factors with levothyroxine treatment may not ultimately translate into a reduction in CVD risk. A recent double-blind, randomized controlled trial that enrolled patients with acute myocardial infarction and SCH in hospitals in the United Kingdom found no difference in the primary outcome of left ventricular ejection fraction at 52 weeks, comparing the 46 participants in the treatment group (levothyroxine 25 mcg daily titrated to serum TSH levels between 0.4-2.5) with the 49 participants in the placebo group (62). An older small study of 40 women with mild SCH randomized participants to 50 mcg of levothyroxine daily or placebo: after 6 months, there was no significant difference in cholesterol, triglycerides, LDL cholesterol, high-density lipoprotein (HDL) cholesterol, body mass index, or other parameters studied (63).…”
Section: Use Of Levothyroxine In Sch To Reduce Cvd Risksmentioning
confidence: 99%
“…Multiple studies have suggested improvement in cholesterol parameters, blood pressure, and various markers of cardiac and vascular structure/function with levothyroxine treatment in SCH (25,(57)(58)(59)(60)(61), but generally these studies were small, the results need to be replicated, and any improvement in CVD risk factors with levothyroxine treatment may not ultimately translate into a reduction in CVD risk. A recent double-blind, randomized controlled trial that enrolled patients with acute myocardial infarction and SCH in hospitals in the United Kingdom found no difference in the primary outcome of left ventricular ejection fraction at 52 weeks, comparing the 46 participants in the treatment group (levothyroxine 25 mcg daily titrated to serum TSH levels between 0.4-2.5) with the 49 participants in the placebo group (62). An older small study of 40 women with mild SCH randomized participants to 50 mcg of levothyroxine daily or placebo: after 6 months, there was no significant difference in cholesterol, triglycerides, LDL cholesterol, high-density lipoprotein (HDL) cholesterol, body mass index, or other parameters studied (63).…”
Section: Use Of Levothyroxine In Sch To Reduce Cvd Risksmentioning
confidence: 99%
“…Although levothyroxine supplementation is easy and convenient for patients with overt hypothyroidism, guidelines do not recommend routine levothyroxine supplementation in asymptomatic patients with subclinical hypothyroidism [26,27]. A recent study on patients with subclinical hypothyroidism and acute myocardial infarction failed to demonstrate the benefit of levothyroxine supplement in improving the left ventricular ejection function [28]. Thus, levothyroxine should not be routinely given to patients with advanced HCC and subclinical hypothyroidism unless future studies prove otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…www.e-enm.org 31 two preliminary but important results were reported from double-blind, randomized controlled trials of LT4 replacement in subjects with subclinical hypothyroidism. Jabbar et al [2] investigated the effects of LT4 in patients with subclinical hypothyroidism presenting with acute myocardial infarction, but failed to show any benefits for outcomes such as left ventricular function, adverse events, and quality of life after 52 weeks of LT4 treatment. Furthermore, de Montmollin et al [3] reported that LT4 replacement failed to improve hypothyroid symptoms or tiredness scores at 1 year in subjects aged ≥65 years with subclinical hypothyroidism (4.6≤ TSH ≤11.9 mU/L) in a secondary analysis of the randomized, placebo-controlled Thyroid Hormone Replacement for Untreated Older Adults with Subclinical Hypothyroidism Trial (TRUST).…”
Section: Health Impacts Of Subclinical Hypothyroidism and The Benefitmentioning
confidence: 99%